Fuel-Mining Exports and Growth in a Developing State: The Case of the UAE - Kalaitzi, Athanasia Stylianou; Chamberlain, Trevor William (International Journal of Energy Economics and Policy, 2020)
This study examines the causal effects of traditional UAE exports on economic growth over the period 1981-2012, using a neoclassical production function augmented with fuel-mining exports and imports of goods and services. To investigate the existence of a long-run relationship between fuel-mining exports and economic growth, the study applies the Johansen cointegration test, while the direction of the short-run causality is examined by applying the Granger causality test in a vector error correction model framework. In addition, a modified Wald test in an augmented vector autoregressive model, developed by Toda and Yamamoto (1995), is used to investigate the existence of a long-run causality between the variables. The cointegration analysis confirms the existence of a long-run relationship between the variables, while fuel-mining exports are found to have a negative impact on economic growth. Moreover, the study finds that fuel-mining exports do not cause economic growth in the short-run or the long-run. Keywords: Exports, Economic Growth, Causality, UAE JEL Classifications: O47, F43, C32 DOI: https://doi.org/10.32479/ijeep.9183